Memantau Toponimi Dan Permasalahannya Di Indonesia - Yusron Halim (Majalah Geografi Indonesia, 1989)
Publications on toponimy in Indonesia are still small in number. The term toponimy has not been widely known by the .society, although the problems that can be observed are among others: inaccuracy in providing geographical names, change in spelling, a great number of local languages, change in names in foreign languages into Indonesian, all of which have given rise to various difficulties, obstacles or confusion in identifying geographical features. In this paper stress is placed on the basic concept of toponimy and the problems of geographical names in Indonesia in the framework of national standardization.